Fault Diagnosis and Fault-Tolerant Control of Megawatt Power Electronic Converter-Fed Large-Rated Asynchronous Hydrogenerator - Joseph, Anto; Chelliah, Thanga Raj; Selvaraj, Raghu; Lee, Kyo Beum (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2019)
In recent years, it has been difficult to achieve power converter redundancy in the multichannel voltage-source inverter (VSI)-fed large-rated doubly fed induction machines (DFIMs), and it has not yet been adopted in any commissioned variable-speed pumped storage power plants. Multichannel VSIs are a fundamental part of DFIMs, and they control the real and reactive powers of the machines. This paper presents the fault-tolerant operation of a large-rated DFIM hydrogenerating unit at open-switch faults in back-to-back VSIs. A technique for diagnosing the open-switch faults in grid-side and machine-side converters is proposed. An open-switch fault is detected based on the variation in rotor currents and dc link voltage, which reduces the computational efforts during fault diagnosis. A 250-MW DFIM with five-channel three-level VSIs (each rated at 9 MVA) is simulated in the MATLAB/Simulink environment to observe the drive behavior. Finally, a 2.2-kW DFIM is tested in a laboratory environment to verify the experimental results.
Keywords: Circuit faults; Doubly fed induction machines; Fault tolerant operations; Fault tolerant systems; Multi channel; Doubly fed induction machine (DFIM); fault diagnosis; fault-tolerant operation; multichannel megawatt voltage-source inverter (VSI); pumped storage power plant (PSPP)